Randomized phase II study of fulvestrant plus palbociclib or placebo in endocrine-sensitive, hormone receptor-positive/HER2-advanced breast cancer: GEICAM/2014-12 (FLIPPER). - Albanell, J.; Martínez-García, M.; Ramos-Boyero, Manuel; O'Connor, Miriam; De-la-Cruz-Merino, Luis; Santaballa-Bertrán, Ana; Martínez-Jáñez, Noelia; Moreno-Antón, Fernando; Fernández, Isaura; Alarcón, Jesús Damián; Virizuela-Echaburu, Javier Antonio; De-la-Haba-Rodríguez, Juan Rafael; et al. (Elsevier, 2022)
Background: The potential benefit of adding palbociclib to fulvestrant as first-line treatment in hormone receptor (HR)-positive, human epidermal growth factor receptor 2 (HER2)-negative endocrine-sensitive advanced breast cancer (ABC) patients remains uncharacterized. Patients and methods: In this randomized (1:1), double-blind, phase II study, postmenopausal women with HR-positive, HER2-negative ABC with de novo metastatic disease or those who relapsed after >12 months of adjuvant endocrine therapy received palbociclib/fulvestrant or placebo/fulvestrant. Stratification was based on recurrent versus de novo metastatic disease and visceral involvement. The primary objective was one-year progression-free survival (PFS-1y) rate. The sample size was 190 patients. The two-sided alpha of 0.2, 80% of power to detect a difference between the arms, assuming PFS rates of 0.695 and 0.545 for palbociclib/fulvestrant and placebo/fulvestrant, respectively. Results: In total, 189 patients were randomized to palbociclib/fulvestrant ([n = 94] or placebo/fulvestrant [n = 95]). 45.5% and 60.3% of patients had de novo metastatic disease and visceral involvement, respectively. PFS-1y rates were 83.5% and 71.9% in the palbociclib/fulvestrant and placebo/fulvestrant arms, (HR 0.55, 80% CI 0.36-0.83, P = 0.064). The median PFS were 31.8 and 22.0 months for the palbociclib/fulvestrant and placebo/fulvestrant arms (aHR 0.48, 80% CI 0.37-0.64, P = 0.001). The most frequent grade 3-4 adverse events were neutropenia (68.1% vs. 0%), leucopenia (26.6% vs. 0%), anemia (3.2% vs. 0%), and lymphopenia (14.9% vs. 2.1%) for the palbociclib/fulvestrant and placebo/fulvestrant, respectively. The most frequent non-hematologic grade 3-4 adverse event was fatigue (4.3% vs. 0%). Conclusions: Palbociclib/fulvestrant demonstrated better PFS-1y rates and median PFS than placebo/fulvestrant in HR-positive/HER2-negative endocrine-sensitive ABC patients.
Este artículo ha sido publicado en la revista European Journal of Cancer. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Mamas - Cáncer - Tratamiento; Palbociclib; Fulvestrant; Endocrine-sensitive; Advanced breast cancer